Methods of amending the state constitutions - McKee, Roland (My University, 1900)
Introduction: A constitution is the framework of an organization; it is the vital organ on which its life depends, and having its origin with the members of that body, it is the principles laid down by them and which all have consented to obey. Charles Borgeand defines “constitution” as, “the fundamental law, according to which the government of a state is organized and the relations of individuals with society, as a whole, is regulated.” The foundation of all republican forms of government is a constitution. Our own government is founded upon a constitution, framed by the fathers of our nation over a century ago. It is “the supreme law of the land,” and all must yield to it. It is an instrument containing only the most general and necessary principles. As our forefathers were laboring over this instrument, and were bending their talent and best strength to perfect it, they realized that time must bring changes, and that change in manners and customs must be accompanied by a corresponding change in the laws and rules which govern the changing body. But, while law must change with manners and customs, yet there are certain principles that are and have been common to man in all ages, and man’s nature is such that it is probable that the future will be but a development of the principles that form the foundation of the present.
Citation: McKee, Roland. Methods of amending the state constitutions. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Political Science; Contitution; Government; Theses